Environmental impact of a design for a solid waste plant in the Francisco Morales Bermúdez market (LACCEI, 2024)
At present, the excessive demand for solid resources is affecting ecosystems and generating negative impacts on the environment, one of these reasons is the generation of solid waste, which is why there is a need to provide methods, techniques and procedures to reduce these impacts. The objective of this study was to analyze the environmental impact of a solid waste plant in the Francisco Morales Bermudez market. For this purpose, a design of a solid waste plant was developed to reduce the negative impacts that operations such as solid waste management and wastewater discharge generate, which is why we used the Conesa matrix to identify the impacts before and after the application of the design. Finally, it was concluded that the application of the solid waste plant design has positive impacts on the environment, i.e. the physical factor, as well as positive impacts on the occupational health of the personnel of the Francisco Morales Bermudez market.